Urgency Of Implementing The Principle Of Recognizing Beneficial Ownership In Government Procurement Of Goods/Services In The Framework Of Preventing Horizontal Tender Collaboration - Amrullah, Andi Ari Setiawan (Jurnal Ilmu Sosial Mamangan, 2024)
There are many forms of unfair business competition regulated in Law Number 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition (Law No. 5 of 1999). One of them is horizontal tender collusion. In practice, this is very easy to do because business actors can collude to arrange or determine who will be the winner of the tender. On the other hand, this can actually be done by one person who has control over existing companies or is termed the beneficial owner of the company. By applying the principle of recognizing the beneficial owner of companies participating in government procurement of goods/services, this can prevent horizontal tender collusion so as to create a conducive business climate and provide a guarantee of equal business opportunities for all business actors